Medicinal and wild food plants of Marmara Island (Balikesir - Turkey) - EMRE, GİZEM (POLSKIE TOWARZYSTWO BOTANICZNE, 2016)
Medicinal and wild food plants have always played an important role in people's lives especially in rural areas. Similar situation can be said for islands due to the reason of them being isolated from mainland. This paper reports an ethnobotanical investigations performed in 2009 and 2014 to determine medicinal and wild food plants of Marmara Island. A total of 30 individuals were interviewed (19 men, 11 women). Totally, 22 plants are recorded as used as traditional folk medicine for the region, and nine of these are also used as a source of wild food. Furthermore, 18 taxa are wild sources of nutrition for the area. The plants most commonly used in the region as medicinal remedies were Salvia fruticosa, Hypericum perforatum, Ficus carica, and Mentha spicata. Plants are mostly used for the treatment of abdominal pain, the common cold, and haemorrhoids. The species most commonly used for food are: Salvia fruticosa, Arbutus unedo, Rhus coriaria, and Rubus sanctus. This ethnobotanical study conducted in this island will enable the traditional use of wild plants both as food sources and herbal remedies to be passed on to future generations.
Keywords: ethnobotany; traditional medicine; wild food plants; Marmara Island; Turkey; EDIBLE PLANTS; ETHNOBOTANICAL SURVEY; PHARMACEUTICAL ETHNOBOTANY; HUMAN CONSUMPTION; TRADITIONAL USES; WEST ANATOLIA; FOLK MEDICINE; PART; PROVINCE; MANISA